Utilization of antenatal services and related factors in aspirational tribal district of eastern Gujarat - Dangi, Shobhana; Shah, Vidhi V.; Kumar, Sanjay; Jain, Prince; Chinchodkar, Kishor N. (International Journal Of Community Medicine And Public Health, 2023)
Background: The number of antenatal visit & timing of first visit are important for health of mother and outcome of pregnancy, it is proved by research studies that earlier registration and regular ANC visits helps in preventing adverse pregnancy outcomes. Various study shows that ANC utilization varies with mothers age, occupation, education, income, parity, place of resident, availability and cost of services. Methods: A Community based cross-sectional study was conducted. The Anganwadi centres were taken as the study area, the study participants were postnatal women up to 42 days after delivery. The primary data collection was done using semi-structured questionnaire by recall method after taking written informed consent. The details of antenatal visits and service utilization were asked. Results: Most of the participants uses the ANC packages however optimal utilization is lacking. 49.24% has taken ≥4 ANC visits. 58.97% have taken ≥180 IFA tablets while 30.40% have visited for their first Ante-natal visit within 12 weeks. Ante-natal mothers who were working and those belonging to lower middle class visited less than 4 times for ante-natal visits. Ante-natal mother below 20 years of age were having lower consumption IFA tablets. >12 weeks for 1st Ante-natal visit was taken by Ante-natal mothers who were working and belonging to middle class. Conclusions: There is suboptimal utilization of the ante-natal service package. Pregnant woman who were daily wage worker as well as middle class and lower class reported less visits and delay in reporting health facility.